Bedtime math - Overdeck, Laura; Paillot, Jim (New York : Feiwel and Friends, 2013)
c
Keywords: Arithmetic -- Problems, exercises, etc. -- Juvenile literature; Mathematical recreations -- Juvenile literature; Mathematics -- Juvenile literature; Arithmetic -- Problems, exercises, etc; Mathematical recreations; Mathematics; Mathematics; Juvenile works